Linguistic Landscape Analysis on Public Signs in Semarapura High Schools: Languages and Scripts Distribution - Pradnyani, Ni Wayan Rasti; Paramarta, I Made Suta; Swandana, I Wayan (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This research analyzed the distribution of languages and scripts on public signs of high schools in Semarapura, at SMA Negeri 2 Semarapura and SMK Negeri 1 Klungkung. Data were collected through observation, photographs, and interviews with principals, teachers, and students using a qualitative descriptive method. A total of 78 signs were collected. The findings showed that most signs were monolingual, with Bahasa Indonesia as the dominant language (71.79%). Bi-script signs using Indonesian with Balinese script, represent 10.26%, while English monolingual signs were relatively rare (2.56%). Bilingual signs were identified, with 7.69% in Indonesian-English and 11.54% in English-Indonesian. Unfortunately, there is no multilingual signs were found. The use of Bahasa Indonesia was the most common on the school signs, which followed national language rules like Law No. 24 of 2009 and Presidential Regulation No. 63 of 2019. The use of Balinese script showed that the schools also followed the local language rule, Bali Governor Regulation No. 80 of 2018. Based on the interviews, the choice of language and script was based on how well the message could be understood, students needed, and efforts to preserve local culture. English was used mainly for academic or international purposes.